2015
DOI: 10.1111/dmcn.12797
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and practicability of the straight leg raise test in children with cerebral palsy

Abstract: ICCIntraclass correlation coefficient ROM Range of motion SDD Smallest detectable difference sEMG Surface electromyography SLR Straight leg raise AIM Preventing restrictions to lower limb movement is part of the treatment given to children with cerebral palsy (CP). Such restrictions can be assessed using the 'straight leg raise' (SLR) test. This study investigated the interrater reliability and practicability of the SLR test in children with CP.METHOD Experienced physiotherapists examined 23 children with CP (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Kreiner highlights the specificity of the SLR test, particularly for patients with nerve root compression requiring surgery. The SLR test can also identify restrictions in the mobility of the sciatic nerve (25). However, determining a standard range for normal SLR is challenging due to variability in intra-individual limb range and demographic factors (24).…”
Section: Discussionmentioning
confidence: 99%
“…Kreiner highlights the specificity of the SLR test, particularly for patients with nerve root compression requiring surgery. The SLR test can also identify restrictions in the mobility of the sciatic nerve (25). However, determining a standard range for normal SLR is challenging due to variability in intra-individual limb range and demographic factors (24).…”
Section: Discussionmentioning
confidence: 99%
“…Further, no norms for neurodynamic functions have been defined in healthy children and youth groups. A few years ago, the reliability of the SLR test was assessed in a group of children with cerebral palsy [20]. Other studies have shown a higher intensity of the sensory response rate in the examination using the long sitting slump (LSS) test in children aged 6-12 years with a migraine or cervicogenic headaches than their healthy peers [21].…”
Section: Discussionmentioning
confidence: 99%
“…A few studies revealed that a limited range of motion in the SLR test might also be applied during the period of childrens' growth [9]. The SLR test was also used in a study of children with cerebral palsy [20]. In addition, the modified long sitting slump test was applied to examine children with headaches compared to healthy controls [21].…”
Section: Introductionmentioning
confidence: 99%
“…Further exclusion criteria were CP with primary athetosis (rather than spastic), surgery of the lower limbs or back within the preceding twelve months and imposed medical restriction for weight bearing. Twenty-one children, who participated in a previous study investigating reliability of the SLR test, did also participate in this study [ 17 ]. The goal was to recruit 30 children.…”
Section: Methodsmentioning
confidence: 99%
“…For this structural differentiation, two test performances were applied in the form of sensitizing movements, first with initial dorsal flexion and second with initial neck flexion. The test was applied according to the test description of a previous study by the authors [ 17 ]. The leg was moved slowly, at approximately 5° per second, as this minimized the influence of (velocity-dependent) spasticity.…”
Section: Methodsmentioning
confidence: 99%